Response from the hospitality sector - Miller, Luther Gordon (Dominica Association of Industry & Commerce RoseauDM, 1993)
Examines the ways travel and tourism is making a contribution to the world, regional and national economies. Concludes that if governments, especially Caribbean governments would recognize the great contribution and adopt responsive policies to expand markets, eliminate barriers to growth and strengthen linkages with other sectors, this contribution could increase substantially, creating greater wealth and jobs.